THE ROLE OF THE UNITED STATES IN JAPAN’S POST-1945 SECURITY ARCHITECTURE (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the results achieved through Japan’s defense cooperation with the United States following the Second World War, and examines security cooperation between the two states during the Cold War and the post-Cold War period. The article also reviews the significance of the San Francisco Peace Treaty, the Yoshida Doctrine, and US military bases in Japan for ensuring Japan’s security.
Keywords: San Francisco Peace Treaty; pacifist constitution; ANPO; Yoshida Doctrine; US military bases in Okinawa; Cold War; Japan security architecture; SCAP; nuclear umbrella